Pengaruh reputasi underwriter, ukuran perusahaan, umur perusahaan, profitabilitas terhadap underpricing saham pada penawaran umum perdana (IPO) di Bursa Efek Indonesia (BEI) periode 2009-2012 - Ricky Riyadi; Sjahruddin '; Akhmad Fauzan Fahtoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study was to analyze the effect of underwriter reputation, firm size, firm age, profitability of the underpricing of shares in an Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) 2009-2012.This study uses a sampling technique with certain criteria, and obtained 59 samples of 83 companies who signed up in the Indonesia Stock Exchange (IDX). The method of analysis used in this study is the method of multiple linear analysis (Multiple Linear Regression) with SPSS version 16.0.From the results of the testing that has been done shows that the variable underwreiter reputation, profitability significant effect on underpricing. While the other variables have no significant effect on underpricingKeywords: Underpricing, underwriter reputation, firm size, firm age,profitability (ROA).